Lipidome disruption in Alzheimer’s disease brain: detection, pathological mechanisms, and therapeutic implications - Sijia He; Ziying Xu; Xianlin Han (Molecular Neurodegeneration)
Abstract Alzheimer’s disease (AD) is among the most devastating neurodegenerative disorders with limited treatment options. Emerging evidence points to the involvement of lipid dysregulation in the development of AD. Nevertheless, the precise lipidomic landscape and the mechanistic roles of lipids in disease pathology remain poorly understood. This review aims to highlight the significance of lipidomics and lipid-targeting approaches in the diagnosis and treatment of AD. We summarized the connection between lipid dysregulation in the human brain and AD at both genetic and lipid species levels. We briefly introduced lipidomics technologies and discussed potential challenges and areas of future advancements in the lipidomics field for AD research. To elucidate the central role of lipids in converging multiple pathological aspects of AD, we reviewed the current knowledge on the interplay between lipids and major AD features, including amyloid beta, tau, and neuroinflammation. Finally, we assessed the progresses and obstacles in lipid-based therapeutics and proposed potential strategies for leveraging lipidomics in the treatment of AD.